2017
DOI: 10.3389/fevo.2017.00149
|View full text |Cite
|
Sign up to set email alerts
|

Early Engagement of Stakeholders with Individual-Based Modeling Can Inform Research for Improving Invasive Species Management: The Round Goby as a Case Study

Abstract: Individual-based models (IBMs) incorporating realistic representations of key range-front processes such as dispersal can be used as tools to investigate the dynamics of invasive species. Managers can apply insights from these models to take effective action to prevent further spread and prioritize measures preventing establishment of invasive species. We highlight here how early-stage IBMs (constructed under constraints of time and data availability) can also play an important role in defining key research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Thus, when these species are introduced into a new region, whether intentionally or accidentally (Gozlan et al 2010a), the data available for predicting their invasiveness are often limited (Top et al 2018), resulting in poorly informed model parameters (Heikkinen et al 2014;Urban et al 2016) and final models with high uncertainty (Parry et al 2013). We showed that monitoring programmes can provide dispersal time series that, when coupled with ABC methods, can help overcome this lack of prior data, enabling more robust predictions of the dispersal dynamics and future invasiveness of the modelled species (Neeson et al 2012;Barros et al 2016;Samson et al 2017).…”
Section: Model Insights Into Bitterling Dispersalmentioning
confidence: 95%
See 4 more Smart Citations
“…Thus, when these species are introduced into a new region, whether intentionally or accidentally (Gozlan et al 2010a), the data available for predicting their invasiveness are often limited (Top et al 2018), resulting in poorly informed model parameters (Heikkinen et al 2014;Urban et al 2016) and final models with high uncertainty (Parry et al 2013). We showed that monitoring programmes can provide dispersal time series that, when coupled with ABC methods, can help overcome this lack of prior data, enabling more robust predictions of the dispersal dynamics and future invasiveness of the modelled species (Neeson et al 2012;Barros et al 2016;Samson et al 2017).…”
Section: Model Insights Into Bitterling Dispersalmentioning
confidence: 95%
“…The platform RangeShifter was used to develop the IBM, as it allows the development of spatially explicit IBMs in which the three key dispersal phases of emigration, transfer and settlement are represented independently (Bocedi et al 2014;Samson et al 2017). A customised version of RangeShifter v. 2.0 was used, which incorporated code to estimate model parameters by ABC given suitable high-level observed data.…”
Section: Ibm Development To Model Bitterling Range Expansionmentioning
confidence: 99%
See 3 more Smart Citations